The Influence of Financial Literacy, Social Environment Factors and Cultural Factors to Consumption Behaviour, (Survey on Faculty 0f Economics Students, Manado State University-Indonesia) - Watung, Sjeddie Rianne (International Journal of Scientific Research and Management (IJSRM), 2018)
This research aims at scrutinizing and analyzing how financial literacy, social environmental factors and cultural factors affect consumption behavior of the students of Economics Education Department, Faculty of Economics Universitas Negeri Manado. The research design applies quantitative approach with survey method. The samples consist of 67 students who are chosen as the respondent by using proportionate stratified random sampling. Research instrument is quetionnaire using likert scale as the measurement, and instruments are tested by using validity and reliability tests (SPSS 16 application). Data analysis includes; 1) descriptive analysis, 2) classical assumption test, and 3) multiple linear regression analysis. The results of research are as follows 1). Financial literacy has a significant influence to consumption behaviour of the students, and the magnitude of financial literacy to consumption behaviour of the students is 33.1%; 2). social environmental factors has a significant influence to consumption behaviour of the students, and the magnitude of social environmental factors to consumption behaviour of the students is 34.91% 3). Social environment factors has a significant influence to consumption behaviour of the students, and the magnitude of social environment factors to consumption behaviour of the students is 32.4%, and 4) Financial literacy, social environmental factors and cultural fctors  have a significant influence to consumption behaviour of the students, and the magnitude of social environmental factors to consumption behaviour of the students is 83.5%. It can be concluded that financial literacy, social environmental factors and cultural factors partially and simultaneously affect consumption behaviour of the students of, Faculty of Economics Universitas Negeri Manado.